Conservation because it pays: shaded Cocoa agroforests in West Africa - Gockowski, J.; Weise, Stephan F.; Sonwa, D.; Tchatat, M.; Ngobo, M. (2004)
The shaded cocoa cropping system found throughout West Africa but particularly well represented in Cameroon and Nigeria is a sustainable agricultural land use system that provides relatively high values of environmental services. The paper describes and quantifies some of its non-cocoa economic and environmental values and examines the economic logic underlying smallholder management. Estimates of these values are developed from field surveys and on-farm research conducted with cocoa producers in West Africa over the last four years. The secondary products evaluated include the fruits of shade trees commonly associated and occupying the mid and upper canopy such as the African plum (Dacryodes edulis) and ndjassang (Ricinodendron heudolotii) along with introduced fruit species such as citrus and avocado. The nutritional contribution of selected associated species such as the bush mango, avocado, wild oil palm (Elaeis guineensis), and African plum is also examined. Timber is another economically important component of the upper canopy, with some species managed and maintained at densities above those found in primary and secondary forests for local exploitation in rural construction. Many medicinal plants are also maintained in the cocoa farm, which often serves as an in-situ herbal pharmacy for the household. The environmental and ecological benefits of these systems include habitat conservation, climate change mitigation, hydrological cycling and watershed protection. The degree to which these services are provided depends in large part on the type and degree of shade maintained as well as their spatial coverage in the landscape. An econometric model of the determinants of shade level explores some of the driving forces behind shade management in Côte d’Ivoire, Ghana, Nigeria, and Cameroon. We conclude by arguing that because of the significant public goods associated with this land use system that there is a need for directed efforts to publicly support the development and maintenance of shaded systems.